2010
DOI: 10.1370/afm.1054
|View full text |Cite
|
Sign up to set email alerts
|

Informed Decision Making Changes Test Preferences for Colorectal Cancer Screening in a Diverse Population

Abstract: PURPOSE We wanted to better understand patient preferences and decision making about options for colorectal cancer screening. Consistency in patient preferences could improve patient-clinician communication about tests by simplifying and focusing discussions. METHODSIn a cross-sectional sample of primary care patients, cognitive ranking tasks were used to estimate patient preferences for fecal occult blood testing, fl exible sigmoidoscopy, colonoscopy, and double-contrast barium enema before and after consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 47 publications
(110 reference statements)
2
50
0
Order By: Relevance
“…Interventions using decision aids to improve patients' decision making about CRC screening have demonstrated improved CRC knowledge and risk perception, have increased intention to be screened, and there are mixed results for improving CRC screening behaviors. [18][19][20][21][22][23][24][25][26] In addition, decision aids have demonstrated that CRC screening test preferences vary by screening test attributes. 22 Patients making informed decisions about CRC screening should have information including: 1) the nature of the clinical decision; 2) the patient's role; 3) alternatives; 4) pros and cons of alternatives; 5) uncertainties associated with the decision; 6) patient's understanding; and 7) patient's preferences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interventions using decision aids to improve patients' decision making about CRC screening have demonstrated improved CRC knowledge and risk perception, have increased intention to be screened, and there are mixed results for improving CRC screening behaviors. [18][19][20][21][22][23][24][25][26] In addition, decision aids have demonstrated that CRC screening test preferences vary by screening test attributes. 22 Patients making informed decisions about CRC screening should have information including: 1) the nature of the clinical decision; 2) the patient's role; 3) alternatives; 4) pros and cons of alternatives; 5) uncertainties associated with the decision; 6) patient's understanding; and 7) patient's preferences.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26] In addition, decision aids have demonstrated that CRC screening test preferences vary by screening test attributes. 22 Patients making informed decisions about CRC screening should have information including: 1) the nature of the clinical decision; 2) the patient's role; 3) alternatives; 4) pros and cons of alternatives; 5) uncertainties associated with the decision; 6) patient's understanding; and 7) patient's preferences. 16,17 In addition, the patients' desire for input from trusted others should be considered in the CRC screening informed decision making (IDM) process.…”
Section: Introductionmentioning
confidence: 99%
“…24 Although we are not aware of other published studies that have compared different methods of values elicitation for CRC screening, several have used explicit techniques to assess key decisional attributes. 13,[25][26][27][28] (Details of these studies are provided in Appendix 5-available online) Most studies have found test accuracy (ability to detect cancer and polyps) to be the most common most important attribute, but the order of importance of other attributes has varied considerably across studies.…”
Section: Discussionmentioning
confidence: 99%
“…10 Further, misunderstandings abound in cancer screening, highlighting an important educational role for primary care; addressing, for example, beliefs that negative test results mean bowel symptoms are less of a concern, or that taking a screening test is an appropriate response to a symptom. There is a recognised role for primary care in promoting informed choice in cancer screening; 11 ideally individuals should make their screening decisions based on the best available information.…”
Section: What Part Can Gps Play?mentioning
confidence: 99%